A unified spatial framework for the evaluation and enhancement of economic potential and efficiency in Cape Town - Kaplan, Jerome (School of Architecture, Planning and Geomatics, 2014)
This dissertation is a comprehensive investigation into the changing morphological and functional structure of the city of Cape Town. Within this it seeks to understand what the economic drivers behind this changing urban form are and what effects this has on Cape Town's economic growth potential, efficiency and resource usage in its management of urban growth. Based on a vast review of economic theories into the changing economic sectoral demands of the city and the locational patterns of activity these engender, the inherent economic potential of differing urban forms and the resource efficiency in management of these forms the conclusion is drawn that currently cities across the globe are facing increasing dispersion and deconcentration of economic activity as they grow. This is despite the resolute finding that higher increased levels of economic agglomeration and concentration within urban areas offers a far higher potential for economic growth, innovation, efficiency and decreased expenditure in management of the urban form. The analysis of Cape Town's morphological and functional structure found that historically Cape Town was monocentric in both of these structural forms. Subsequently however rampant dispersal of economic activity which was shown to be driven by a structurally rigid low density stratified distribution of population has led to the incremental entrenchment of a low economic land intensity concentration outside of the historic CBD in a typical polycentric form. This it is shown represents a economically and resource use inefficient form of the city, which inevitably will stagnate future economic and metropolitan performance. It was further established that functionally, Cape Town still retains a strong monocentric structure however this too seems to be dissipating. Based on these findings of Cape Town's current structural inefficiencies and future projections, the dissertation reviews the current spatial development framework prepared by the Cape Town Municipality. The findings of this critique indicate a long term structure plan which does not adequately address the inefficiencies identified in the analysis section. It further finds conflicting rationalities in the approach to long term spatial planning that will not likely promote a more economically efficient urban structure. Based on these critiques the dissertation of recommendations on how urban planning can better promote an increasingly efficient and rational economically approach to the urban structure of Cape Town, thereby answering the primary question set out at the beginning of through dissertation.